Pré-Sal: Petróleo e políticas públicas no Brasil (2007-2016) - Martinez, Paulo Henrique [UNESP]; Colacios, Roger Domenech (Fronteiras: Journal of Social, Technological and Environmental Science, 2016)
The article analyses the relationship between social policy and economy in Brazil from the pre-salt exploration to the present day. The announcement of oil reserves in the pre-salt layer resulted in rapid changes in the economic, social and legal perspectives for the country in the first two decades of the twenty-first century. The new range of national oil production would be the basis of an agenda of economic and social development in the terms of office of Lula and Dilma. In their respective terms, both promoted reformulations in the oil regulation. The legislation was amended with regard to contract models, royalty distribution and reserves control, ensuring the federal government greater sovereignty in the extraction, refining and distribution of oil. The legislative and policy change aimed at the allocation of part of the pre-salt profits for investments in infrastructure and sectoral policies for human development in Brazil.
Pre-Salt: Oil and public policies in Brazil (2007-2016)
Keywords: Environmental history; Oil; Pre-salt; Public policies